「自主學習」的圖像、實踐與反思：從實驗理念到課程轉化 A Study of Pictures, Practices and Reflections on “Self-Regulated Learning”: From Experimental Ideas to Curriculum Transformation - 王俊斌 Chun-Ping Wang (Journal of Curriculum Studies, 2019)
本研究以「自主學習」為焦點，首先，以種籽親子實驗國民小學與苗圃蒙特梭利中小學為對象，分析不同實驗教育機構對於「自主」理念的不同想像，並釐清學校制度及其課程規劃的轉化歷程。其次，以臺北市公辦公營臺北市大安區和平實驗國民小學為例，探究公辦公營模式的實驗理念建構，以及其課程發展與教學實踐的連結作法。最後，本研究綜合前述分析，對於十二年國民基本教育與實驗教育共同關注的「自主學習」圖像，提出綜合性的檢討與建議。 This article focuses on the idea of “self-regulated learning” and main purposes are as follow: firstly, analyzing pictures of “self-regulated learning” of two experimental institutions, Seeding School and Miao-Pu Montessori School, and inquiring their transformative mechanisms of school institution and curriculum plan; secondly, taking Taipei Municipal Ho-Ping Experimental Elementary School as the other example, exploring the construction of experimental education concept of this public management of public school, and its curriculum development and teaching transformative process; finally, synthesizing this paper’s comprehensive analysis and providing some suggestions on the idea understanding of “self-regulated learning,” for the 12-year basic education and experimental education.